Effect of emotional intelligence on auditors’ judgment and audit sustainability: Empirical evidence from Vietnam - Hai-Thanh Phan; Phu-Huu Nguyen; Cuong-Thanh Nguyen; Tien-Thuy Thi Vo; Tung-Thanh Nguyen (Problems and Perspectives in Management, 2021)
This paper aims to measure the influence of emotional intelligence on auditors’ judgment and the sustainability of audit activities in the Vietnamese market through auditors’ perceptions. Data were collected through interviews using questionnaires from 232 auditors who currently work for independent audit firms in many provinces and cities. The research methods used include Cronbach’s Alpha test, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The study showed that 5 of 5 factors of emotional intelligence positively affect the auditors’ judgment. These are intrapersonal awareness competency, interpersonal relationship capability, stress management ability, environment adaptability potentiality, and mood creativity focus. Meanwhile, only 4 of 5 factors of emotional intelligence positively influence the audit sustainability of audit projects (excluding interpersonal relationship capability). The study also shows that the auditor’s judgment has a positive influence on audit sustainability. Besides, there is a great difference related to the emotional intelligence and its impact on auditor’s judgment and audit sustainability based on gender. The study’s results provide scientific evidence that human factors, especially emotional intelligence, influence the auditor’s judgment and the sustainability of his/her professional career. Acknowledgment The authors would like to thank the Editor-in Chief and a reviewer for their helpful comments that in our view have helped to improve the quality of the manuscript significantly.